PENGARUH KUALITAS PELAYANAN, FASILITAS, DAN LOKASI TERHADAP KEPUTUSAN KONSUMEN DALAM MEMILIH LEMBAGA PENDIDIKAN BBC - ETS - Taufik Hidayat; Saryadi Saryadi; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2013)
BBC - ETS is educational institutions and English language training that aims to provide services and English language training so that communities are able to communicate in English fluently. This study aimed to determine the effect of service quality, facilities and location of the consumer's decision in choosing the institution BBC - ETS Tlogosari Semarang branch. The population in this study is the teenager and adult students. By Sugiyono theory (2008), taken 95 respondents to be sampled and the sampling technique used is the proportional stratified random sampling. Measurement scale using Likert scale. In the analysis of the data using simple linear regression and multiple regression. Research shows that the quality of service, facilities, and location of positive influence on the decision to select a course, either partially or simultaneously. Categories of service quality by 57.9 percent said either. Category known facilities by 40 percent expressed either. Categories location by 42.1 percent said either. decision to select a course known by 41.1 percent expressed high. service quality affects the decision to choose a course of 38.1 percent. Variables facilities influence the decision to choose a course of 16.6 percent. Variables affect the location decision of choosing a course of 12.1 percent. Variable quality of service, facilities, and location influence the decision to choose a course of 43.3 percent.